Law, infrastructure, and human rights - Likosky, Michael (Cambridge University, 2013)
This book analyzes how human rights are handled in varied contexts and then assesses the feasibility of a common international institutional solution under the auspices of the United Nations to the alleged problem of the inability to translate human rights into practice.